Failure to respond to instruction to submit catch-up program for the period from September 4, 2018 to January 15, 2019 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the failure to respond catch-up program for the period from September 4, 2018 to January 15, 2019 of BRAC University new campus project.